Recognition of Marriage by Repute: Its Implications on Customary Law and Gender Justice in Malawi - Mbano-Mweso, Ngcimezile; Malunga, Bernadette; Makanje, Gift; Chome, Theresa (Southern African Public Law)
Since 1995, the Constitution of Malawi has recognised marriage by repute or cohabitation as a form of marriage in the country. However, it was only in 2015 that the Marriage, Divorce and Family Relations Act formalised such a marriage by providing a criterion for courts by which the existence of the marriage can be determined. The authors argue that this Act reflects upon society by accepting this form of marriage even in traditional society. Through discourse analysis and doctrinal research methodology, the article traces how the initial concept of a valid marriage has changed to accommodate and recognise this form of marriage. Even before the statutory law had operationalised this form of marriage, traditional leaders, as a way of determining the validity of marriages, clothed these unions with some rights ordinarily attached to married people. Customary law is not static but changes over time even in a process of cross-fertilisation with statutory law, where each is culpable of being shaped and also shaping the other. The recognition of marriage by repute has changed the marriage terrain in Malawi where eighty per cent of marriages are contracted under customary law, providing gender justice for women who were initially disadvantaged when such unions were not regarded as valid marriages by not complying with formal marriage requirements in terms of custom. Such women lost all rights afforded to a wife and the necessary benefits that she would have had in a valid marriage.